2009 IEEE International Ultrasonics Symposium 2009
DOI: 10.1109/ultsym.2009.5441709
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subharmonic emission from encapsulated microbubbles as an indicator for sonoporation of cell monolayers

Abstract: Sonoporation is the ultrasound induced transient opening of cell membranes. Large scale oscillation of nearby microbubbles (MBs) is considered to be the primary effect in sonoporation whereas MB destruction correlates with lower sonoporation efficiency and increased cell damage. The scale of MB oscillation in a cloud can be determined by monitoring subharmonic emission. In this study, SW480 cells are grown in Opticell containers, which are filled with a growth medium containing SonoVue MBs and propidium iodide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…It is believed when a bubble is driven at this resonant frequency, it reaches the highest oscillation amplitude and may provide more effective therapeutic re- (44). The subharmonic emissions for Sonovue MB was studied at 3 and 30 cycle pulse duration and have shown that the emissions were higher at longer pulse duration of 30 cycles (45). Beside these the time dynamics of MBs at these varying acoustic conditions hasn't been investigated which is the focus of this thesis.…”
Section: Microbubble Acoustic Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed when a bubble is driven at this resonant frequency, it reaches the highest oscillation amplitude and may provide more effective therapeutic re- (44). The subharmonic emissions for Sonovue MB was studied at 3 and 30 cycle pulse duration and have shown that the emissions were higher at longer pulse duration of 30 cycles (45). Beside these the time dynamics of MBs at these varying acoustic conditions hasn't been investigated which is the focus of this thesis.…”
Section: Microbubble Acoustic Behaviourmentioning
confidence: 99%
“…These unique markers of the MB characteristics are associated with bubble dynamics. Investigations on sub-harmonics imaging (54; 44) and in therapy (45) have shown that subharmonic emission can be exploited as indicator of sonoporation. Although the mechanism behind subharmonic-ultraharmonic emissions are not well understood, four possi-ble explanation have been suggested for free bubbles: (i) transient cavitation, (ii) subharmonic oscillation of bubbles excited at resonance, (iii) resonant oscillations of bubbles excited at their second harmonic and (iv) non-radial modes of oscillation.…”
Section: Higher Harmonics (Nf )mentioning
confidence: 99%
“…The subharmonic emission of 5 different agents at high frequency (25 MHz) have been investigated and have shown that with increase of pulse duration the subharmonic emissions are enhanced for all agents (44). The subharmonic emissions for Sonovue MB was studied at 3 and 30 cycle pulse duration and have shown that the emissions were higher at longer pulse duration of 30 cycles (45). Beside these the time dynamics of MBs at these varying acoustic conditions hasn't been investigated which is the focus of this thesis.…”
Section: Effect Of Acoustic Parameters On Mb Behaviourmentioning
confidence: 99%
“…This is increased by the presence of microbubbles (MBs). Effective temporal membrane permeability implicates large scale MB oscillation with subsequent dissolution [1], [2]. High excitation pressure amplitudes cause violent MB destruction which often results in high numbers of dead cells, whereas low pressure amplitudes cause low sonoporation rates [3].…”
Section: Introductionmentioning
confidence: 99%